2000
DOI: 10.1046/j.1523-1755.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant versus natural human 111In-β2-microglobulin for scintigraphic detection of Aβ2m amyloid in dialysis patients

Abstract: Scintigraphy for Abeta2m with 111In-labeled rhbeta2m provides a homogenous and safe recombinant protein source and leads to enhanced sensitivity and lower radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…As a consequence of renal failure, the concentration of circulating ␤ 2 m increases by up to 60-fold (21). Through a mechanism that is not fully understood, the full-length, wild-type, disulfide oxidized protein then self-assembles to form amyloid fibrils that typically deposit in and around osteoarticular sites (22,23). Despite the identification of ␤ 2 m as the causative agent of DRA more than 20 years ago (17), there are currently no therapies for the disorder other than organ transplantation or other surgical procedures (24), an option that is only available for a minority of patients.…”
mentioning
confidence: 99%
“…As a consequence of renal failure, the concentration of circulating ␤ 2 m increases by up to 60-fold (21). Through a mechanism that is not fully understood, the full-length, wild-type, disulfide oxidized protein then self-assembles to form amyloid fibrils that typically deposit in and around osteoarticular sites (22,23). Despite the identification of ␤ 2 m as the causative agent of DRA more than 20 years ago (17), there are currently no therapies for the disorder other than organ transplantation or other surgical procedures (24), an option that is only available for a minority of patients.…”
mentioning
confidence: 99%
“…It has been recently shown that scintigraphy in which the radioactive tracer (iodine 131 or indium 111) is labeled to the amyloid precursor protein ␤ 2 -microglobulin is superior to MRI in demonstrating deposition of ␤ 2 -microglobulin amyloid in dialysis patients. 13,14 This is particularly so when recombinant human ␤ 2 -microglobulin is used as the labeling agent. 14…”
Section: Discussionmentioning
confidence: 99%
“…This also includes the uptake in the spleen and liver which is also observed in other In‐labeled proteins. Thus, this new tracer is as specific for organs containing Aβ 2 m‐amyloid as natural β 2 m as no tracer was fixed in organs lacking amyloid and no fixation above background has been noted in patients without amyloidosis [21].…”
Section: Discussionmentioning
confidence: 99%